The Role of The Central Bank on Economic Growth (Study Case: Indonesia) - Wijaya, Asyadia Haq Zahra; Ismail, Munawar; Santosa, Dwi Budi (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Since the last decade, Indonesia had a relatively low economic growth performance compared to several countries in Southeast Asia. To encourage economic growth in Indonesia, the role of the central bank is one of the policies that need to be considered. Therefore, this study aims to analyze the role of the central bank, especially in controlling inflation, exchange rates, and interest rates on economic growth. This study uses the ARDL method to ensure short-term and long-term relationships between variables. The results showed that there is a short-term and long-term relationship between interest rates and exchange rates on economic growth. This study also finds that there is no significant relationship between inflation and economic growth in both the short and long term. This analysis shows various central bank policies to stimulate economic growth such as exchange rates and interest rates.